Effective of diode laser on teeth enamel in the teeth whitening treatment - U. Klunboot (2018)
This research purpose is to investigate the changing of teeth color and to study the surface of teeth after treatment by laser diode at different power densities for tooth whitening treatment. In the experiment, human-extracted teeth samples were divided into 7 groups of 6 teeth each. After that laser diode was irradiated to teeth, which were coated by 38% concentration of hydrogen peroxide, during for 20, 30 and 60 seconds at power densities of 10.9 and 52.1 W/cm2. The results of teeth color change were described by the CIEL*a*b* systems and the damage of teeth surface were investigated by scanning electron microscopy (SEM). The results showed that the power density of the laser diode could affect the whiteness of teeth. The high power density caused more luminous teeth than the low power density did, but on the other hand the high power density also caused damage to the teeth surface. Therefore, the laser diode at the low power densities has high efficiency for tooth whitening treatment and it has a potential for other clinical applications. © 2011 SPIE-OSA-IEEE.